Perceptible Components of the Dental Professional as Determiners of the Costs of Services - Morales-García, Manuel Higinio; Sotaminga-Calderón, Ricardo Josué; López-Wade , Arístides; Morales-Magaña, Juan (Horizonte Sanitario, 2024)
Objectives: Identify the perceptible components in setting the costs of dental services considering the professional's perspective.Materials and methods: An exploratory, descriptive and cross-sectional qualitative research was conducted among dental surgeons in Villahermosa, Tabasco. A discretionary sample size of 350 participants was established. A planning cost survey of the dental clinic was applied from February to July 2022. The instrument was organized in three sections: pricing, office operation and administration. SPSS version 25 was used for data analysis.Results: 22.8% dental surgeons mentioned that the pricing of dental treatments highlights the work time considered to perform the treatment and 51% referred to the fact that there is no balance in the treatment process and the costs of production. Whereas 54.28% said they had no administrative skills.Conclusion: Dentists lack the basic management skills to manage resources, achieve better performance in the exercise of his profession, be competitive, innovative and entrepreneurial in a dynamic market.Keywords: Cost allocation; Hospital administration; Dental services; Organization and administration.